Orofacial myofunctional changes in skeletal Class III patients after bimaxillary orthognathic surgery. Issue 9 (September 2022) - Bai, Yuanyan; Tang, Yanglu; Ren, Mingjun; Wang, Maolan; Zhao, Wenli; Zeng, Ting; Liu, Fan; Zhu, Songsong
Abstract: The aim of this study is to investigate the effect of bimaxillary orthognathic surgery on orofacial myofunctional changes in skeletal class III patients. 35 patients who received Le Fort I maxillary advancement osteotomy and mandibular SSRO setback were included in this study. Facial expression function was analyzed by "placid" or "smile" expressions using chL-chR, ∠chRnchL, and ls-li. Occlusal force and balance were analyzed using a T-scan III digital occlusal analysis system. Maximum mouth opening (MMO) was measured prior to surgery and 2/14/28/42/90/180/360 days after surgery. After surgery, patients recovered facial expressions in no less than 3 months for both the "placid" or "smile" facial expression. Patients obtained significantly improved 'smile' expressions 3 months after the operation compared to preoperative "smiles", and this improvement remained stable 12 months after the operation. Occlusal force was significantly decreased with the balance of occlusion lost immediately after surgery. These conditions gradually recovered, and patients finally obtained a more balanced and stronger occlusion [occlusion balance: 6.7 ± 2.7 mm vs. 4.1 ± 3.0 mm (day -7 vs. day 42); occlusion force: 19.6 ± 7.0 kg vs. 24.2 ± 9.3 kg (day -7 vs. day 180)]. However, patients had smaller postoperative mouth opening compared to preoperation opening during our follow-up. Our results confirmed that orthognathic surgery obstructs orofacial myofunctions of skeletal class III patients in the short-term. In the long-term, orthognathic surgery results in more stable and balanced orofacial myofunctions. By understanding the process of functional recovery of orofacial muscles after orthognathic surgery, we hope to accelerate patient's recovery from surgery.